Analisis Kesalahan Berbahasa Tataran Fonologi dan Tataran Morfologi Ragam Krama pada Karangan Deskripsi Karya Siswa Kelas X (Jurusan Bahasa dan Sastra Jawa Universitas Negeri Semarang, 2022)
During the Field Experience Practice (PPL), many language errors were found in students' essays. This study describes the errors in Javanese language in the descriptive essay of the work of class X students of SMA N 12 Semarang. The approach used is a qualitative descriptive approach combined with the theory of language error analysis. The research data are in the form of descriptive essays in Javanese variety of manners. The source of this research data is the students of Class X SMA N 12 Semarang which contains language errors. The data were collected using the listening and note-taking technique, while the data analysis techniques used in this study were sorting and dressing techniques. The results showed that there were 4 language errors at the phonological level, namely 78% vowel phoneme errors, 17% consonant phoneme errors, 3% consonant addition errors, and 2% consonant reduction errors. Meanwhile, at the morphological level there are 6 errors, namely errors because prefixes are separated from basic words as much as 17%, errors due to suffixes being separated from basic words as much as 5%, errors in prefixing as much as 11%, ater-ater hanuswara errors 21%, diction errors as much as 24%, and reduplication errors as much as 22%. Keywords: descriptive essay; Javanese manners; language error